Proportion of CD4 and CD8 tumor infiltrating lymphocytes predicts survival in persistent/recurrent laryngeal squamous cell carcinoma. (February 2018) - Hoesli, Rebecca; Birkeland, Andrew C.; Rosko, Andrew J.; Issa, Mohamad; Chow, Kelsey L.; Michmerhuizen, Nicole L.; Mann, Jacqueline E.; Chinn, Steven B.; Shuman, Andrew G.; Prince, Mark E.; Wolf, Gregory T.; Bradford, Carol R.; et al.
Highlights: We explored the prognostic role of biomarkers in recurrent LSCC after RT/CRT. Immunohistology included CD4, CD8, PDL-1, p16, CD31, Vimentin, EGFR, and p53. Elevated levels of CD8, CD4 positive TILs were associated with improved DSS and DFS. CD4, CD8 status may be an important prognostic biomarker in this subset of patients. Abstract: Tumor infiltrating lymphocytes (TILs) have been shown to be an important prognostic factor in patients with previously untreated head and neck cancer. After organ preservation therapy for laryngeal cancer and subsequent persistence/recurrence, the prognostic value of TILs is unknown. Our goal was to determine if TILs have value as a prognostic biomarker in patients with surgically salvageable persistent/recurrent laryngeal squamous cell carcinoma. Levels of TILs were quantified on tissue microarrays from 183 patients undergoing salvage total laryngectomy for persistent/recurrent laryngeal cancer after radiation or chemoradiation between 1997 and 2014. Demographic and clinical data were abstracted. Immunohistology evaluation included CD4, CD8, PDL-1, p16, CD31, Vimentin, EGFR, and p53. Elevated levels of either CD8 or CD4 positive TILs were associated with improved disease specific survival (CD8: HR 0.46, 95% CI 0.24–0.88, CD4: HR 0.43; 95% CI 0.21–0.89) and disease free survival (CD8: HR 0.53, 95% CI 0.29–0.94, CD4: HR 0.52; 95% CI 0.27–0.99). Levels of CD8 (HR 0.74; 95% CI 0.47–1.17) or CD4 (HR 0.66; 95% CI 0.40–1.08) TILs were not significantly associated with overall survival. In bivariate analysis, patients with elevated CD4 and/or CD8 TILs had significantly improved disease specific survival (HR 0.42; 95% CI 0.21–0.83) and disease free survival (HR 0.45; 95% CI 0.24–0.84) compared to patients with low levels of CD4 and CD8. PDL-1, p16, CD31, Vimentin, EGFR, and p53 were not significant prognostic factors. On multivariate analysis, elevated CD8 TILs were associated with improved disease specific survival (HR 0.35; 95% CI 0.14–0.88, p = .02) and disease free survival (HR 0.41; 95% CI 0.17–0.96, p = .04). CD8, and possibly CD4, positive TILs are associated with favorable disease free and disease specific survival for recurrent/persistent laryngeal cancer.